Preventive Effects of Velvet Antler (Cervus elaphus) against Lipopolysaccharide-Induced Acute Lung Injury in Mice by Inhibiting MAPK/NF-κB Activation and Inducing AMPK/Nrf2 Pathways. (2nd January 2018) - Chang, Jui-Shu; Lin, Hung-Jen; Deng, Jeng-Shyan; Wu, Wen-Tzu; Huang, Shyh-Shyun; Huang, Guan-Jhong
Abstract : Velvet antler ( Cervus elaphus ) is a typical traditional animal medicine. It is considered to have various pharmacological effects including stimulation of the immune system, increase in the physical strength, and enhancement of sexual function. This paper aims to investigate the aqueous extract of velvet antler (AVA) in the mouse models of LPS-induced ALI. Inhibition of NO, TNF- α, IL-1 β, IL-6, and IL-10 productions contributes to the attenuation of LPS-induced lung inflammation by AVA. A 5-day pretreatment of AVA prevented histological alterations and enhanced antioxidant enzyme activity in lung tissues. AVA significantly reduced the material (total number of cells and proteins) in the BALF. Western blot analysis revealed that the expression of iNOS and COX-2 and phosphorylation of I κ B- α and MAPKs proteins are blocked in LPS-stimulated macrophages as well as LPS-induced lung injury in mice. Consistent with this concept, the phosphorylation of CaMKK β, LKB1, AMPK, Nrf2, and HO-1 was activated after AVA treatment. The results from this study indicate AVA has anti-inflammatory effects in vivo and AVA is a potential model for the development of health food. In addition, its pathways may be at least partially associated with inhibiting MAPK/NF- κ B activation and upregulating AMPK/Nrf2 pathways and the regulation of antioxidant enzyme activity.